Gold nanomaterials – The golden approach from synthesis to applications - Homa Hassan; Pradakshina Sharma; Mohd. Rahil Hasan; Shiwani Singh; Deepanshi Thakur; Jagriti Narang (Materials Science for Energy Technologies, 2022)
Materials at nanometer scale with special attributes like compact size, large surface ratio, and quantum effect are quite distinct from their bulk counterparts. With the advancement of nanoscience and nanotechnology, innumerable inorganic nanomaterials including semiconductor, metal or metal oxide and carbon, nanomaterials have been designed. The optical, physiochemical, electrical, and biological features of gold nanomaterial make it one of the most widely employed nanomaterials. Gold nanoparticles have a long history in chemistry, going all the way back to the ancient Roman era when they utilized to decorate glasses by staining them. Since the physicochemical properties of gold nanomaterials can be modified by varying their structural dimensions attained by various fabrication processes, gold nanomaterials are suitable contender for colorimetric analysis, biosensor, photothermal transducers and imaging. For decades, scientists have been studying the controlled fabrication of gold nanomaterials as their characteristics and function are extremely reliant on the shape and dimensions of the particle. Gold nanomaterials have shown its potential use in numerous fields like biomedicine and biosensors due to their controllable synthesis steps, lower toxicity, high biocompatibility, adjustable optoelectrical properties, and uncomplicated surface modification. These advantages make gold nanomaterials suitable for a wide range of applications, from the biomedical to the energy and environmental sectors. The application section of this review includes a summarized synopsis of these applications in broader terms. In terms of shape, this paper covers a variety of synthetic methods for producing different gold nanomaterials. The morphologies of gold nanomaterials which includes nanoparticles, nanorods, nanoclusters, nanowire, nanoflower and nanosphere have also been discussed in this paper with the emphasis of recent research projects.